Regional factors associated with pneumococcal vaccination coverage among U.S. adults with underlying chronic or immunocompromising conditions - Junqing Liu; Linda Shoener Dunham; Kelly D. Johnson (Taylor & Francis Group, 2023)
The Centers for Disease Control recommends pneumococcal vaccination for U.S. adults aged 19-64 years with chronic or immunocompromising conditions, however, vaccination coverage is low and regional variations in coverage are rarely studied. This study examined pneumococcal vaccination coverage at the metropolitan statistical area (MSAs) level and identified regional factors associated with pneumococcal vaccination using the combined IBM® Watson Health MarketScan® Commercial and Medicare Supplemental databases. Pneumococcal vaccination coverage, clinical and socioeconomic factors were calculated for each MSA. Ordinary least square and spatial regression models were used to examine factors associated with vaccination. Results indicated that the national pneumococcal vaccination coverage was 13.4% with a large variation across MSAs (0-34%). The spatial error model, model with the best fit, showed that proportions of the population who were ≥50 years of age, received an influenza vaccine, or had health maintenance organization health plans were positively associated with pneumococcal vaccination coverage. In summary, we found that national pneumococcal vaccination coverage was low and there was substantial variation across MSAs. Regional factors identified may help inform interventions to improve pneumococcal vaccination coverage across geographies.